Ecological Impacts and Management Strategies of Acacia melanoxylon Species in the African Ecosystems - Kiptoo, T. K.; Ole Kiyapi, J. L. (Africa Environmental Review Journal, 2022)
Alien invasive plants can alter ecosystem services, reducing biodiversity and having negative social and economic consequences. The leguminous Acacia melanoxylon is one of the most problematic acacia tree species native to Australia on a global scale. The invasive species is currently invading the forest ecosystem in Africa, with severe consequences for ecosystem services. There have been very few reviews of the ecological effects of Acacia melanoxylon species on the ecosystems of African forests. Consequently, it is necessary to comprehend its ecological effects and management strategies to mitigate its negative effects. Scopus, Web of Science, and Google Scholar were used to conduct an exhaustive bibliographic search for scientific and technical articles as well as government documents on Acacia melanoxylon species invasions in African countries and documented management strategies. The ecological effects include reduced species diversity and local seed dispersal of the tree layer. The rapid spread of A. melanoxylon in forest areas has the potential to alter the forest structure and composition. Additionally, it affects the growth and spread of forest plant species. The proposed management strategies of A. melanoxylon include uprooting young shoots and applying herbicide to the stumps of mature trees to prevent regrowth. Herbicide-coated bark (basal bark methods) can also be effective. Ring barking can be utilized to kill large trees. Young plants can be sprayed with foliar solutions. The study provides baseline information regarding the ecological impacts and management strategies of Acacia melanoxylon, which serves as a management tool for the preservation of native species. The study recommends implementing policies, legislation, and incentives to guide public and private investment in controlling invasive alien plant species and passive or active restoration as needed. Additionally, this study recommends further research to address the deficiency in species management and its ecological impact on the Eastern and Southern parts of Africa.